Depressive vulnerability in women with Alzheimer's disease: relationship with personality traits and abnormal personality dimensions - Henqriques-Calado, J.; Duarte-Silva, M. E.; Sousa Ferreira, A. (Journal of Affective Disorders, 2018)
Background: This study sought to determine the evaluation of current and pre-morbid depressive vulnerability dimensions in Alzheimer's disease. Sidney Blatt's personality developmental perspective, the Five-Factor model and Axis II personality disorders were taken as references. Methods: The study was conducted with two groups which were assessed using the Depressive Experiences Questionnaire, the NEO-FFI and the Personality Diagnostic Questionnaire-4 +, in the form of individual interview sessions. Current personality measure: Alzheimer's disease Group, consisting of 44 female participants (M-Age = 81.36 years); Pre-morbid personality measure: Alzheimer's disease Group Informants (n = 40). Results: Self-Criticism personality vulnerability is a general indicator of psychopathology. In pre-morbidity, Neuroticism (beta = 0.41), Agreeableness (beta = -0.63) and Conscientiousness (beta = -0.08) predicted Self-Criticism, explaining 64% of the variance; additionally, Self-Criticism (beta = 0.72) and Neediness (beta = 2.05) predicted the PDQ-4 + total, explaining 58% of the variance. In terms of current personality, the PDQ-4 + total was predicted by Self-Criticism (beta = 0.55), explaining 30% of the variance. Limitations: The small size of the samples, especially since it is difficult to access individuals diagnosed with AD at the onset or in its early stages; measuring personality changes by means of retrospective assessment by proxies may have introduced some memory bias. Conclusions: These findings are relevant to research relating depressive vulnerability to personality traits and psychopathology in Alzheimer's disease.